Pembuatan Iklan Promosi Perpustakaan Padang Panjang untuk Anak Melalui Media Motion Graphic - Wilhelmina, Grace; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractThis article discusses the making of Padang Panjang library promotion advertisement for children through motion graphic media. The purpose of writing describes the making of motion graphics to introduce to children. There are 6 stages of making motion graphic as follows: (1) concept or concept, is the stage before making motion graphic, (2) drawing or design, is the stage of making motion graphic more specifically visualized in the form of images, (3) Collection of material or material collecting, is a collection of material in the making of motion graphics, (4) assemblies or assemblies, which are made in several stages, namely designing, animating, compositing, and rendering carried out by using applications, (5) testing or testing the video made, (6) distribution or distribution, is the final stage of packaging and distribution of the product.Keywords: children;Â library;Â motion graphic.Â